2021
DOI: 10.21037/atm-21-4404
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery-to-pulmonary artery fistula in adults: evaluation with 320-row detector computed tomography coronary angiography

Abstract: Background: To analyze the imaging features of coronary artery-to-pulmonary artery fistula (CPAF) on coronary computed tomography angiography (CCTA).Methods: This was a retrospective study of 3,975 patients who underwent 320 row detector CCTA examinations in our hospital from May 2015 to July 2020. A total of 22 patients who diagnosed with CPAF were reviewed for CCTA imaging characteristics, including the origin, number, blood volume, opening size, and course of fistula vessels, and the drainage site, size, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 5 As a result, a CPAF in most cases is found to be located on the left anterolateral side of the PA, with the remaining showing no dominant portion. 3 , 5 In the present patient, the CPAF originating from the LAD formed an aneurysm, whereas CPAF originating from the RCA was small and did not show communication to the aneurysm. Based on those findings, the origin of the fistula from the LAD was ligated, and the drainage site in the PA was closed.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“… 5 As a result, a CPAF in most cases is found to be located on the left anterolateral side of the PA, with the remaining showing no dominant portion. 3 , 5 In the present patient, the CPAF originating from the LAD formed an aneurysm, whereas CPAF originating from the RCA was small and did not show communication to the aneurysm. Based on those findings, the origin of the fistula from the LAD was ligated, and the drainage site in the PA was closed.…”
Section: Discussionmentioning
confidence: 41%
“…Although 19% to 29% of CPAF cases have been reported to be complicated with an aneurysmal dilatation, rupture of a CPAF aneurysm is rare. 1 , 3 Generally, coronary artery aneurysm larger than 3 cm in size is an indication for surgery because of risk of rupture. 4 However, in patients with an aneurysm associated with a CPAF, some reports have noted a ruptured aneurysm sized 1 to 2 cm, the same as found in the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large CAF fistulous diameter may lead to high shunts as well as high coronary blood flow, resulting in a high likelihood of aneurysm. Hang et al [ 18 ] have reported a similar conclusion that the average diameter of the fistula in the aneurysm group was significantly larger than that in the CAF without aneurysm group (2.99 ± 1.37 vs 2.54 ± 1.67). However, no significant difference was identified between the two groups in their study ( P = 0.499), which may be due to the small sample size of patients in the two groups (n = 8 vs 14).…”
Section: Discussionmentioning
confidence: 75%
“…The calculated incidence of aneurysm formation was 59.09%. It was reported that all fistulas resulted from a single drainage area with an average diameter of 2.81 ± 1.48 mm, and the diameter of the fistula with an aneurysm was larger than that without an aneurysm [ 4 ]. It has been reported that more than half of the patients with a coronary-pulmonary arteriovenous fistula were asymptomatic, and the fistula connecting the coronary artery to the pulmonary artery could have single or multiple origins.…”
Section: Introductionmentioning
confidence: 99%